Void fraction correlations for vertical upward two-phase flow in pipes - Ghajar, Afshin J. 1951- (Knovel, 2011)
"Vertical upward two-phase flow in pipes is found commonly in industries involving oil and gas production, water treatment, nuclear reactors, and geothermal systems. Whether the two-phase flow exists in the form of different components (e.g., air and water) or occurs as a result of phase change caused by evaporation or condensation of a single fluid, the void fraction is an important parameter in the analysis of pressure drop, heat transfer, and mass transfer. Since vertical upward two-phase flows are relatively common in industry, void fraction correlations that can provide the greatest degree of accuracy need to be sorted out"--Description from Knovel site.